Development of Leptolyngbya sp. BL0902 into a model organism for synthetic biological research in filamentous cyanobacteria - Gao, Hong; Wang, Yali; Huang, Ziling; Yu, Feiqi; Hu, Xi; Ning, Degang; Xu, Xudong (Frontiers in Microbiology, 2024)
Cyanobacteria have great potential in CO2-based bio-manufacturing and synthetic biological studies. The filamentous cyanobacterium, Leptolyngbya sp. strain BL0902, is comparable to Arthrospira (Spirulina) platensis in commercial-scale cultivation while proving to be more genetically tractable. Here, we report the analyses of the whole genome sequence, gene inactivation/overexpression in the chromosome and deletion of non-essential chromosomal regions in this strain. The genetic manipulations were performed via homologous double recombination using either an antibiotic resistance marker or the CRISPR/Cpf1 editing system for positive selection. A desDoverexpressing strain produced γ-linolenic acid in an open raceway photobioreactor with the productivity of 0.36 g.m -2 .d -1 . Deletion mutants of predicted patX and hetR, two genes with opposite effects on cell differentiation in heterocyst-forming species, were used to demonstrate an analysis of the relationship between regulatory genes in the non-heterocystous species. Furthermore, a 50.8-kb chromosomal region was successfully deleted in BL0902 with the Cpf1 system. These results supported that BL0902 can be developed into a stable photosynthetic cell factory for synthesizing high value-added products, or used as a model strain for investigating the functions of genes that are unique to filamentous cyanobacteria, and could be systematically modified into a genome-streamlined chassis for synthetic biological purposes.